ASSESSMENT OF ECONOMIC EFFICIENCY OF APPLICATION OF RALTEGRAVIR BY PATIENTS WITHOUT EXPERIENCE OF TYPE 1 HIV INFECTION THERAPY IN RUSSIA - Elamin H. Elbasha; Elena Aleksandrovna Pyadushkina; Maria Vladimirovna Avxentyeva; Alexander Gennadievich Tolkushin; Maxim Yurievich Frolov (Фармакоэкономика, 2015)
The purpose of the work performed was assessment of cost efficiency of Raltegravir within the schemes of antiretroviral therapy as compared to the schemes on the basis of drugs from the group of protease inhibitors with adult patients with Type 1 HIV infection (HIV-1) that have no experience of treatment.Materials and methods. In the Markov's model developed for assessment of long-term clinical and economic indicators of efficiency of Raltegravir with adult patients with HIV-1 that have no experience of antiretroviral therapy, pharmacoeconomic analysis of "costs and benefits" was performed in accordance with recommendations of the Panel on Cost-effectiveness in Health and Medicine and with consideration of requirements of specialized Russian manuals. Direct costs for application of the schemes compared were calculated on the basis of applicable norms of financing of the Russian Federation. Consumptions of health care resources and life standard indicators were determined on the basis of foreign studies regarding each of the 18 states of health provided with Markov's model and distinguished according to the number of CD4 cells and viral load.Study results. It was demonstrated that Raltegravir within schemes of antiretroviral therapy of the first line, as compared to the schemes on the basis of drugs from the group of protease inhibitors with subsequent second line therapy on the basis of non-nucleoside reverse transcriptase inhibitors (including Raltegravir in addition to the optimized treatment at the last stage), was a more cost efficient alternative as it had clinical benefits with affordable additional expenses. The increment cost efficiency rate (ICER) per a year of saved life with consideration of its quality comprised 1,097,078 rubles without exceeding the threshold of readiness to pay for a year of quality life equal to 3 GDP per capita.